Mesostructured silica nanoparticles supported electrosynthesized goethite in cationic surfactant for photodegradation of 2–chlorophenol - Rohayu, Jusoh (2015)
2–chlorophenol (2–CP) which had been widely used in industry and daily life is a priority toxic pollutant that has caused considerable damage to the aquatic ecosystem and human health. Due to this reason, continuing study on efficient catalyst for degradation of this recalcitrant pollutant has been conducted in these recent years. In this study, goethite (α–FeOOH) was synthesized by an electrochemical method in a cationic surfactant solution and subsequent impregnation with mesostructured silica nanoparticles (MSN) gave α FeOOH/MSN. The catalysts were characterized using X–ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform–infrared (FT–IR), 29Si magnetic angle spin nuclear magnetic resonance (29Si MAS NMR), nitrogen physisorption analysis, electron spin resonance (ESR), and X–ray photoelectron spectroscopy (XPS). The results indicate that the cationic surfactant was retained around α– FeOOH surface with a free swinging alkane tail pointing outward from the catalyst. The performance of the catalysts were tested on the photodegradation of the 2–CP in a batch reactor under visible light irradiation. The results showed that the α FeOOH were able to inhibit electron–hole recombination to give complete degradation of 50 mg L−1 2–CP at pH 5 when using 0.03 g L−1 catalyst and 0.156 mM of H2O2. In contrast, it was found that by introducing the α–FeOOH to the MSN support, sequential silica removal in the MSN framework and isomorphous substitution of Fe ion was occurred, which able to effectively degrade the 2–CP with degradation percentage of 92.2, 79.3, 73.1, and 14.2%, with the loading of α–FeOOH in the following order: 10 wt% > 15 wt% > 5 wt% > MSN, respectively. Beside the retainment of the cationic surfactant structure on the catalysts, the MSN was also elucidated to play an important role as an electron acceptor that enhanced the electron–hole separation. Response surface methodology (RSM) analysis for the α– FeOOH and α–FeOOH/MSN catalysts showed good significance of model with low probability values (<0.0001) and a high coefficient of determination (R2). The kinetic studies of both catalysts illustrated that surface reaction was the controlling step of the process. Reusability study showed that both catalysts were still stable after more than 4 subsequent reactions. The upscaling study using 10–fold upscale system indicate superior performance of the catalysts with almost complete degradation of 2–CP. The employment of the catalysts on degradation of various pollutants such as phenol, cationic dye and anionic dye has also showed remarkable performance, suggesting the potential use of the catalysts for various applications. Significantly, the synthesis method of these catalysts could be a great advantage in the future development of nanotechnology.